Sensory phenotypes provide insight into the natural course of diabetic polyneuropathy - Tsilingiris, Dimitrios; Schimpfle, Lukas; Rauchhaupt, Ekaterina von; Sulaj, Alba; Seebauer, Lukas; Herzig, Stephan; Szendrödi, Julia; Kopf, Stefan; Kender, Zoltán (Diabetes, 2024)
We aimed to investigate the characteristics and longitudinal course of sensory phenotypes identified through quantitative sensory testing (QST) in the frame of diabetic sensorimotor polyneuropathy (DSPN). A total of 316 individuals with diabetes were examined (type 2 diabetes 78.8%), 250 of whom were undergoing follow-up visits at 1, 2, and/or 4 (2.88 ± 1.27) years. Allocation into four sensory phenotypes (healthy, thermal hyperalgesia [TH], mechanical hyperalgesia [MH], and sensory loss [SL]) at every time point was based on QST profiles of the right foot. Cross-sectional analysis demonstrated a gradual worsening of clinical and electrophysiological sensory findings and increased DSPN prevalence across the groups, culminating in SL. Motor nerve impairment was observed solely in the SL group. Longitudinal analysis revealed a distinct pattern in the developmental course of the phenotype (from healthy to TH, MH, and finally SL). Those with baseline MH exhibited the highest risk of transition to SL. Reversion to healthy status was uncommon and mostly observed in the TH group. Among those without DSPN initially, presence or future occurrence of SL was associated with a three- to fivefold higher likelihood of DSPN development. Our comprehensive longitudinal study of phenotyped patients with diabetes elucidates the natural course of DSPN. QST-based sensory examination together with other tools for phenotyping may be useful in determining the natural course of diabetic neuropathy to identify patients at high risk of DSPN and guide preventive and therapeutic interventions.The course of diabetic sensorimotor polyneuropathy (DSPN) development, from healthy status to overt DSPN, is poorly understood.We studied the characteristics and longitudinal appearance of lower-extremity sensory phenotypes (healthy, thermal hyperalgesia [TH], mechanical hyperalgesia [MH], and sensory loss [SL]) identified through quantitative sensory testing in individuals with diabetes.There was an increasing severity and patterned order of longitudinal appearance across healthy, TH, MH, and SL phenotypes. SL was most strongly associated with formal DSPN.Our findings provide insight into the natural history of DSPN. Sensory phenotyping can be implemented to identify high-risk individuals and those most likely to benefit from therapeutic interventions.
Gesehen am 17.06.2024